Legal Implications of Enforcement of the Supreme Court Circular Number 2 of 2023 on the Civil Rights of Interfaith Marriages - Rahayu, Sulis (PT FORMOSA CENDEKIA GLOBAL, 2023)
Law Number 1 of 1974 regulating Marriage, Article 21 paragraph (3), has the legal loophole that has permitted couples of different religions and beliefs to seek acknowledgment of the legitimacy and register their marriage through a court ruling. By presenting a certificate of the rejection, the parties whose marriage is denied have the right to obtain a decision from the court in the region where the marriage registrar's officer holding the rejection of the marriage is located. The enactment of Law 23 of 2006 concerning Population Administration has increased the chances for married couples adhering to diverse religious and ideological beliefs to obtain legal recognition for their union. The marriage registrar's office will no longer be able to register marriages for married couples of various religions due to the adoption of Supreme Court Circular Letter Number 2 of 2023.